Synthesis and Characterizations of 1-D Double-Chain Manganese Coordination Polymer [Mn(ncpo)(H2O)3]n - YU, WEI (Asian Journal of Chemistry, 2010)
A 1-D double-chain manganese coordination polymer constructed by 2-nitro-4-carboxylphenoxy acetic acid has been synthesized by phase diffuse method. The crystal structure has been determined by X-ray diffraction. The crystal is monoclinic, space group Cc with a = 9.647(10), b = 25.46(3), c = 6.560(7) Å, β = 131.741(11)°, MnC9H11NO10. Mr = 348.13, V = 1202(2) Å3, Dc = 1.923 g/cm3, F(000) = 708, μ = 1.156 cm-1 and Z = 4. The final refinement gave R = 0.0695 and wR = 0.1755 for 1307 reflections with I > 2σ(I). The coordination polymer demonstrates 1-D double-chain structure along a axis and it is connected to 3-D supramolecular network by hydrogen bonds. Except for hydrogen bonds, there exist π-π stacking interactions among benzene rings. The complex begins to lose water molecules at 433 K and when it is heated to 693 K, it will lose nitro group and oxyacetate radical.